Implementation strategies for embedding patient-reported outcome and experience measures (PROMs/PREMs) in routine care: secondary analysis of an umbrella review - Fontaine, Guillaume; Ramos, Joshua; Mooney, Meagan; Perron, Marie-Eve; Crump, Laura; Lambert, Sylvie D. (Université d'Ottawa | University of Ottawa, 2026)
Abstract Background Routine capture of patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs) is championed as core infrastructure for learning health systems and value-based care. Yet, the guidance on how to implement these measures is scattered. We synthesised evidence on implementation strategies used to introduce and sustain PROMs and PREMs, and examined how these strategies align with common barriers and stages of implementation. Methods We conducted a secondary analysis of an umbrella review (25 reviews; 1086 primary studies, 2014–2023) that catalogued implementation determinants and processes of PROMs and PREMs. Two reviewers independently coded implementation strategies using the 73-item Expert Recommendations for Implementing Change (ERIC) taxonomy. Strategies were temporally mapped to the phases of the Exploration–Preparation–Implementation–Sustainment (EPIS) framework, and onto the barriers identified in the parent review using the CFIR × ERIC matching tool. Results Twenty of 25 reviews reported at least one implementation strategy, yielding 152 instances coded to 43 of 73 ERIC strategies. Pre-implementation strategies (74 instances) focused on local consensus building, readiness and barrier assessments, early IT integration, and front-loaded education and champion preparation. During implementation and sustainment (78 instances), the strategies most often used were audit and feedback, real-time data feedback to clinicians, reminders, facilitation, technical assistance, refresher training, and patient onboarding and prompts. Mapping strategies to key barriers showed reasonable coverage for workflow, staff capability, and organisational fit, but gaps for patient capability, long-term financing, data analytics, and equity. Thirty ERIC strategies were not identified, most relating to policy, financing, or market-shaping. Conclusion Implementing PROMs and PREMs in routine care requires coordinated changes in relationships, workflows, technology, and incentives. This study organises existing evidence into practical tools that health system teams and researchers can use to select, sequence, and resource implementation strategies for PROM and PREM programmes.